An assessment of the records and the records management practices of the University of the Philippines Computer Center - Bernardo, Jose Paolo P.; Lagrama, Eimee Rhea C. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
This is study is an assessment of the records and the records management practices of the University of the Philippines Diliman Computer Center (UCC). It determined and enumerated the records and records management practices of UCC, assess them and documented any problems were encountered while handling them. A guided answering of the survey questionnaire and an inventory of the records were conducted from March 20 May 7, 2018 at the UCC office. The persons primarily in charge of the records were the respondents of this study.
This study found out that UCC maintain records as old as the 1970s and has no document or manual used in handling and disposing such records. This study concluded that UCC is not compliant with existing standards on records management. Thus, it recommends that UCC should take steps in complying to such standards. As a product of the records inventory and the survey, a File Plan and Records Retention and Disposition Schedule were created. Being a government office, UCC is expected to adhere with the transparency and accountability campaigns of the national government. Hence, an effective records management should be followed by UCC in order to meet this.
Thesis
Keywords: University of the Philippines Diliman -- Computer Center; Records -- Management